The roles of grouper TAK1 in regulating the infection of Singapore grouper iridovirus. Issue 124 (May 2022) - Zhang, Luhao; Kang, Shaozhu; Chen, Hong; Liao, Jiaming; Sun, Mengshi; Wu, Siting; Xu, Zhuqing; Xu, Linting; Zhang, Xin; Qin, Qiwei; Wei, Jingguang
Abstract: Transforming growth factor-β activated kinase 1 (TAK1) is a member of the mitogen-activated protein kinase family. It is an upstream factor of the IκB kinase, which activates IKKα and IKKβ. TAK1 is a key factor in the induction of nuclear factor κB (NF-κB) and plays a crucial role in the activation of inflammatory responses. However, the roles of TAK1 during viral infection in teleost fish are largely unknown. In this study, we cloned a TAK1 homolog (HgTAK1) from the hybrid grouper ( Epinephelus fuscoguttatus ♂ ×  Epinephelus lanceolatus ♀). The open reading frame of HgTAK1 consists of 1728 nucleotides encoding 575 amino acids, and the predicted molecular weight is 64.32 kDa HgTAK1 has an S_TKc domain, which consists of a serine/threonine protein kinase and a catalytic domain. Expression pattern analysis showed that HgTAK1 was distributed in all tested tissues, with abundant contents in the heart, head kidney, and blood. Additionally, HgTAK1 was distributed in the cytoplasm of grouper spleen (GS) cells. After Singapore grouper iridovirus (SGIV) infection, the expression of HgTAK1 increased in GS cells. Overexpression of HgTAK1 could promote the replication of SGIV in GS cells and inhibit the activation of NF-κB and IFN stimulated response elements (ISRE) in reporter assay. When co-expressed with IRF3 or HgIRF7 in GS cells, HgTAK1 obviously down-regulated IRF3- or IRF7-mediated the NF-κB and ISRE promoter induction. The interaction between HgTAK1 and IRF3 or IRF7 has been identified by co-immunoprecipitation assay. These findings provide a basis for understanding the innate immune mechanism of the grouper response to viral infection. Highlights: HgTAK1 was distributed in all tested tissues, with abundant contents in the heart, head kidney, and blood. HgTAK1 promoted SGIV replication in GS cells. HgTAK1 down-regulated IRF3- and IRF7-mediated interferon immune response.